Role of Teachers and Learners in TBL (Sharada Research Journal, 2026)
The modern concept of Teaching Learning givens important factor for the learning in developing experience and skill. TBL fosters teachers, learners, textbook compiler, and curriculum designer to cultivate this approach, as cognitive approach have become compulsory in today’s competitive era. To meet modern learning demands, initiators began escaping their manuals as task-based, and many course designers explains their new concept of subject followed the TBL concept — although few lacked a vivid perception of the difference between work-based and task-released learning. It aims to analyze and show the merits and demerits of this method, while also discussing the elements that proceed to its foster and the different types of work and activities commonly used in classrooms.